Implementasi Prinsip Tawasuth, Tawazun, dan Tasamuh dalam Kegiatan Keagamaan di Ponpes Al-Manshuriyah Plered-Purwakarta - Arna Gusnia; Dudun Bahrul.H; Fanasita Filiang; Herny Indriasari; Ismy Nurazizah (RISOMA : Jurnal Riset Sosial Humaniora dan Pendidikan, 2026)
This study aims to describe the implementation of the principles of tawassuth, tawazun, and tasamuh in religious activities at Islamic boarding school Al-Manshuriyah Plered-Purwakarta, as well as to analyze the supporting factors, challenges, and their impact on shaping the moderate character of the the students. This research employs a qualitative approach with a descriptive method. Data were collected through observation, interviews, and documentation. The findings indicate that the implementation of Ahlussunnah wal Jama’ah (Aswaja) values has been carried out effectively through various programs such as routine Islamic study sessions, Qur’an reading, congregational prayer, commemoration of Islamic holidays, and social-religious activities. The principle of tawassuth is reflected in the congregation’s moderate attitude in understanding religious texts, tawazun is demonstrated through the balance between worship activities and social engagement, while tasamuh is manifested through harmonious interactions and appreciation of differences. Supporting factors include visionary leadership and a conducive learning environment, whereas inhibiting factors involve the diverse backgrounds of community members and limited facilities. The implementation of Aswaja values has positively contributed to the development of moderate, tolerant, and religious character among the congregation. This study reinforces the importance of Islamic boarding school as a center for cultivating Wasathiyah-based Islamic character in society.